Post-translational site-selective protein backbone α-deuteration - Galan, S; Wickens, J; Dadova, J; Ng, W; Zhang, X; Simion, R; Quinlan, R; Pires, E; Paton, R; Caddick, S; Chudasama, V; Davis, B (Springer Nature, 2018)
Isotopic replacement has long-proven applications in small molecules. However, applications in proteins are largely limited to biosynthetic strategies or exchangeable (for example, N-H/D) labile sites only. The development of postbiosynthetic, C-1H → C-2H/D replacement in proteins could enable probing of mechanisms, among other uses. Here we describe a chemical method for selective protein α-carbon deuteration (proceeding from Cys to dehydroalanine (Dha) to deutero-Cys) allowing overall 1H→2H/D exchange at a nonexchangeable backbone site. It is used here to probe mechanisms of reactions used in protein bioconjugation. This analysis suggests, together with quantum mechanical calculations, stepwise deprotonations via on-protein carbanions and unexpected sulfonium ylides in the conversion of Cys to Dha, consistent with a 'carba-Swern' mechanism. The ready application on existing, intact protein constructs (without specialized culture or genetic methods) suggests this C-D labeling strategy as a possible tool in protein mechanism, structure, biotechnology and medicine.